Effect of Surgical Intervention on Neurologic Recovery in Patients with Central Cord Syndrome - Du, Li; Zhao, Shichang; Zhu, Zhongsheng; Xue, Feng; Zhang, Yadong (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
To review the experience of managing central cord syndrome (CCS) surgically, we retrospectively reviewed 71 patients from October 2015 to April 2017. Deteriorating neurologic status with evidence of radiologic compression and spinal instability were absolute indications for surgery. The American Spinal and Injury Association (ASIA) motor scores (AMS) were recorded at the time of admission (aAMS), 3 days postoperatively (3dAMS), 1 month postoperatively(1mAMS), and at final follow-up (fAMS). Analysis of variance was performed to compare 3dAMS, 1mAMS, and fAMS. Surgery was successful in all 71 patients without re-injury of the spinal cord, infection, or other perioperative complications. The postoperative AMS at 3 days, 1 month, and at the final follow-up significantly improved over preoperative scores. ASIA sensory scores at fAMS were significantly better than 3dAMS and1mAMS scores. The ASIA motor and sensory scores at 1mAMS showed no significant improvements compared with the 3dAMS. Therefore, for patients diagnosed with CCS, combined with evidence of radiologic compression and spinal instability, surgery was beneficial in terms of gains in neurologic recovery.
Keywords: central cord syndrome; incomplete spinal cord injury; cervical spine; surgical decompression